CMOS-MEMS thermoelectric generator for low power medical devices - Rahman, Z.H.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents the design and simulation of a new concept of CMOS-MEMS thermoelectric generator (TEG) capable of converting thermal energy into electrical energy for use in low power medical devices. The TEG is designed with three unique features that will ensure optimum heat transfer that result in achievement of larger temperature difference between two junctions. First, a thicker dielectric layer is designed between two metal layers. Second, trenches isolation is introduced to isolate the hot and cold junction area. Third, thermal insulator and heat sink layer are deposited on the top surface of the TEG at the hot and cold junction area, respectively. Based on the simulation results of these three abovementioned features, a device with size of 25 mm2 consisting of 1712 thermocouples with 5 K temperature difference between two sides, is capable of producing output voltage and power of 3.294 V and 0.925 Î¼W, respectively. Voltage factor is 2.635 Vcm-2K-1 and power factor is 0.148 Î¼Wcm-2K-2. Â© 2015 IEEE.